Study on the effect of NAT10 on the polarization of macrophages in mice - ZHANG Xianzhong; WANG Haicheng; CHEN Yongliang; WANG Zuolin (Kouqiang hemian waike zazhi)
[Objective:] To investigate the effect of N-acetyltransferase 10 (NAT10) gene on the polarization of mouse macrophages in vitro and in vivo. [Methods:] Mouse monocyte line RAW264.7 cells were cultured in vitro and induced by polarization, and the expression level of NAT10 was observed using real-time quantitative polymerase chain reaction (RT-qPCR). The NAT10 inhibitor Remodelin hydrobromide was used to inhibit the expression of NAT10, and its effect on the polarization of RAW264.7 cells was observed. A model of periodontitis was established using silk thread ligation, while Remodelin hydrobromide was injected simultaneously. The mice were randomly divided into control group, periodontitis group, control medication group and periodontitis medication group. After 7 days, their mandibles were taken for RT-qPCR, micro-CT analysis and histological staining. [Results:] NAT10 was highly expressed in mouse M2 macrophages. Compared with the control group, the periodontitis group showed decreased NAT10 expression in alveolar bone tissue, along with reduced proportions of NAT10-positive cells in the furcation area and lower percentages of NAT10/F4/80 double-positive cells. The concentration gradient experiment showed that 10 μmol/L Remodelin hydrobromide had the best inhibition efficiency. After adding Remodelin hydrobromide, the expression of M1 macrophage-associated genes increased and M2 macrophage-associated genes decreased in RAW264.7 cells. Inhibition of NAT10 expression enhanced alveolar bone destruction in a mouse model of periodontitis; the proportion of CD86-positive cells at the root bifurcation increased; the proportion of CD163-positive cells decreased. [Conclusion:] The expression of NAT10 significantly increased in RAW264.7 cells after M2 polarization, and significantly decreased in the mouse periodontitis alveolar bone. Inhibiting the expression of NAT10 can promote M1 polarization of macrophages, inhibit M2 polarization, and notably exacerbate alveolar bone destruction in mice with periodontitis.